2015
DOI: 10.1002/mabi.201500060
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin Bc-Bearing Hydrophilic Photosensitizer Conjugate for Photodynamic Cancer Theranostics

Abstract: The accurate diagnosis and proper therapy for cancer are essential to improve the success rate of cancer treatment. Here, we demonstrated that the vitamin Bc -bearing hydrophilic photosensitizer conjugate folic acid-polyethylene glycol-pheophorbideA (FA-PEG-PheoA) has been synthesized for the intracellular diagnosis and photodynamic therapy of a tumor. The synthesized vitamin Bc -bearing hydrophilic photosensitizer conjugate has been characterized for the folic acid receptor expressing the ability to target tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Additionally, they are biocompatible and have physical properties that are similar with living tissues [100]. In addition, hydrogels can possibly be used for applications delivery of hydrophilic PSs for PDT, including PAD-S31 (13,17-bis(1-carboxypropion)carbamoylethyl-3-ethenyl-8-ethoxyiminoethylidene-7-hydroxy-2,7,12,18-tetramethyl-porphyrin sodium), Mono- l -aspartyl chlorin, FA-PEG-PheoA, and aluminum (III) phthalocyanine chloride tetrasulfonic acid (Al-4), among others [101,102,103].…”
Section: Nanotechnology-based Drug Delivery Systemsmentioning
confidence: 99%
“…Additionally, they are biocompatible and have physical properties that are similar with living tissues [100]. In addition, hydrogels can possibly be used for applications delivery of hydrophilic PSs for PDT, including PAD-S31 (13,17-bis(1-carboxypropion)carbamoylethyl-3-ethenyl-8-ethoxyiminoethylidene-7-hydroxy-2,7,12,18-tetramethyl-porphyrin sodium), Mono- l -aspartyl chlorin, FA-PEG-PheoA, and aluminum (III) phthalocyanine chloride tetrasulfonic acid (Al-4), among others [101,102,103].…”
Section: Nanotechnology-based Drug Delivery Systemsmentioning
confidence: 99%
“…Synthesis and Characterization of PEG‐Ce6 : Ce6 was conjugated with PEG based on a previously reported procedure of the group . Bifunctional PEG 5 kDa (COOH, OH) (200 mg, 40 µmol) was dissolved in 2 mL of DCM.…”
Section: Methodsmentioning
confidence: 99%
“…To compare the cellular uptake of different targeting moieties, folic acid conjugated PEG‐Ce6 was prepared. Folic acid and purified PEG‐Ce6 were conjugated via a conventional carbodiimide method as previously reported by the group . To verify the nucleolin‐mediated cellular uptake of Aptamer‐PEG‐Ce6, all cells (1 × 10 5 cells per well in a 6‐well cell culture plate) were treated with Aptamer‐PEG‐Ce6 at various concentrations (0–10 µg mL −1 ) for 2 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vitamin B receptor is overexpressed in a various human tumors . Our group has previously reported that folate is an effective marker for use with cancer targeted delivery carriers …”
Section: Introductionmentioning
confidence: 99%